Is there a survival benefit within a German primary care-based disease management program? - Miksch, Antje; Laux, Gunter; Ose, Dominik; Joos, Stefanie; Campbell, Stephen; Riens, Burgi; Szecsenyi, Joachim (The American journal of managed care, 2010)
OBJECTIVE: To compare the mortality rate of patients with type 2 diabetes who were enrolled in the German diabetes disease management program (DMP) with the mortality rate of those who were not enrolled. - STUDY DESIGN: This observational study was part of the ELSID study (Evaluation of a Large Scale Implementation of disease management programs) in Germany. - METHODS: Participants had type 2 diabetes and were either enrolled or not enrolled in the DMP. The DMP provides systems-based, multifaceted, and patient-centered interventions. To reduce imbalances between the groups, a matched sample was created using sex, age, retirement status, federal state, pharmacy-based cost groups, and diagnostic-cost groups as matching criteria. Cox proportional hazards regression model and the Kaplan-Meier method were used to assess overall mortality. The observation period was 3 years beginning on January 1, 2006. - RESULTS: A total of 11,079 patients were included in the analysis. As of January 1, 2006, 2300 patients were enrolled in the DMP and 8779 were receiving routine care. There were 1927 matched pairs of patients in the DMP group and the non-DMP group. The overall mortality rate was 11.3% in the DMP and 14.4% in the non-DMP group (log-rank test P <.01). - CONCLUSIONS: We found an association between participation in the German diabetes DMP and reduced mortality. This reduced mortality cannot be attributed directly to the DMP. However, further research should evaluate whether a primary care-based DMP contributes to increased life expectancy in patients with diabetes.
Gesehen am 26.04.2023